Persistence and adherence to single-tablet regimens in HIV treatment: a cohort study from the French National Healthcare Insurance Database. (22nd April 2015) - Raffi, François; Yazdanpanah, Yazdan; Fagnani, Francis; Laurendeau, Caroline; Lafuma, Antoine; Gourmelen, Julie
Abstract: Objectives: To compare adherence and persistence (continuous treatment with a prescribed medication) in HIV adult patients who received combination ART (cART) as a once-daily single-tablet regimen (STR) versus other administration schedules. Methods: A representative random sample of the French National Healthcare Insurance Database was used. Adherence and persistence were compared according to their administration schedules using χ 2 and survival analyses. STRs were marketed in France in 2009 and the study period was selected to allow a sufficient number of patients with an STR and a relevant duration of follow-up. Results: During the period covered (2006–11), 362 HIV-positive adult antiretroviral-naive patients (566 lines of treatments) were selected. The mean rates of adherence were 89.6% for the STR (tenofovir/emtricitabine/efavirenz; n  = 76), 86.4% for cART with >1 pill once daily ( n  = 242) and 77.0% for cART with >1 daily intake ( n  = 248; P  < 0.0001 versus STR). Kaplan–Meier estimations of persistence after 2 years of treatment were 79.1% for the STR, 53.3% for cART with >1 pill once daily and 51.8% for cART with >1 daily intake ( P  = 0.001; log-rank test). Sensitivity analyses confirmed these results. After excluding treatment sequences showing a switch from tenofovir/emtricitabine plus efavirenz to the similar STR, the rates of persistence were 80.3% for the STR ( n  = 60), 77.3% for atazanavir-containing cART ( n  = 96) and 68.3% for darunavir-containing cART ( n  = 56) at 18 months (global P  = 0.006). Conclusions: These results suggest that persistence is higher in HIV patients treated with an STR compared with other administration schedules. Significant benefit in terms of adherence was observed with the STR in comparison with regimens with >1 daily intake but no difference was observed when comparing with regimens involving >1 pill once daily.